(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the new educational paradigm proceeds from the fact that the development of lifelong learning skills is a continuous process, the importance of self-development competence of a chemistry teacher, stages of self-development, factors, experience — An analysis of the results of a survey conducted during experimental work is provided.